Impact of guided inquiry-based laboratory experiments on secondary school students’ attitudes toward biology in Ethiopia: A quasi-experimental study - Ashebir Mekonnen Chengere; Beyene Dobo Bono; Samuel Assefa Zinabu; Kedir Woliy Jilo (PLoS ONE, 2025)
Attitude plays a vital role in achieving modern science education goals by enhancing students’ conceptual understanding, motivation, academic performance, interest, and engagement in scientific inquiry. However, in many Ethiopian schools, attitudes toward science are often overlooked, and traditional teacher-centered instruction combined with limited resources hampers their development. To address these issues, this study examined the effect of Guided Inquiry-Based Laboratory Experiments Enriched Instruction (GIBLEI) on secondary school students’ attitudes toward biology, using a quasi-experimental design with pretest-treatment-posttest phases. Two biology classes from purposively selected Ethiopian secondary schools were randomly assigned to an experimental group (EG, N = 46) and a control group (CG, N = 29). Over eight weeks, the EG received GIBLEI, while the CG experienced Traditional Laboratory Experiments Enriched Instruction (TLEI). Attitudes were measured using a 5-point Likert scale. The results showed that GIBLEI significantly improved students’ overall attitude toward biology, enthusiasm for biology, perception of biology as a course, and understanding of biology as a process, compared to TLEI. However, it did not significantly affect their views of biology as a career. GIBLEI also promoted gender inclusivity by reducing attitude differences between male and female students. These findings highlight the benefits of GIBLEI in fostering positive attitudes, engagement, and inclusivity in biology education, enhancing both student outcomes and equity in science learning.